The inefficiency of the Justice in Portugal: causes and consequences - Jesus-Silva, Natacha (2018)
Given the breach of trust that the justice system in Portugal is facing, it is fundamental to analyse the reasons why the judicial system is considered inefficient. This study contributes to the identification of the underlying factors that contribute most to the inefficiency of justice in Portugal by analysing the frequency of the most relevant contents enunciated by the participants. The survey consists of two parts: the first consists of the following socio-demographic variables: occupation, region, age, gender and remuneration; the second consists of an open question, to which participants can state which factors contribute most to the ineffectiveness of justice in Portugal. The answers obtained were submitted to a content analysis with the aim of identifying the content underlying the inefficiency of justice in Portugal, with 18 subcategories emerging according to the contents expressed by the participants. In this way, the way above all of simplification, justice will go to what really matters: efficiency, celerity and transparency.